1992
DOI: 10.1073/pnas.89.17.7910
|View full text |Cite
|
Sign up to set email alerts
|

Hagfish humoral defense protein exhibits structural and functional homology with mammalian complement components.

Abstract: A genomic clone and cDNA fragment encoding a portion of a humoral recognition molecule from the aglish were isolated and sequenced. The serum protein has previously been described as having structural features that are immunoglobulin-like. Amino acid sequence obtained from the 77-kDa Hi heavy chain facilitated the isolation of a genomic clone containing at least two coding regions. The hagfish is an agnathan, a modem representative of the earliest evolved group of vertebrates, the ostracoderms or jawless fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…However, many years of similar attempts to isolate homologous genes from the most primitive vertebrate, cyclostomes, have failed. What was earlier believed to be immunoglobulin molecules in hagfish turned out to be one of the complement proteins (Hanley et al, 1992;Ishiguro et al, 1992). It is now probable that rearranging variable-region genes of immunoglobulins and T-cell receptors (TcRs) are absent in cyclostomes.…”
Section: A Possible Link Of Jaws With Adaptive Immunitymentioning
confidence: 99%
“…However, many years of similar attempts to isolate homologous genes from the most primitive vertebrate, cyclostomes, have failed. What was earlier believed to be immunoglobulin molecules in hagfish turned out to be one of the complement proteins (Hanley et al, 1992;Ishiguro et al, 1992). It is now probable that rearranging variable-region genes of immunoglobulins and T-cell receptors (TcRs) are absent in cyclostomes.…”
Section: A Possible Link Of Jaws With Adaptive Immunitymentioning
confidence: 99%
“…The CP activity can be assayed by determining the amount of serum required to hemolyse a given number of sensitized sheep red blood cells (SRBC), whereas the AP activity is measured in the same manner, but by using rabbit red blood cells (RaRBC) instead of sensitized SRBC. It has been demonstrated that functionally and structurally similar complement components are present in all non-mammalian vertebrates such as birds (Ohta et al ., 1983;Kai et al ., 1983), reptiles (Vogel et al ., 1984;Koppenheffer, 1987), amphibians (Sekizawa et al ., 1984) and fish including hagfish and lamprey, the most primitive class of extant vertebrates (Koppenheffer, 1987;Hanley et al ., 1992;Nonaka et al ., 1984a, b). It has also been shown that complement components are present in invertebrates such as tunicate and sea urchin Al-Sharif et al ., 1998;Smith et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Both lamprey and hagfish are able to produce humoral factors in response to a number of antigens. First described as antibody-like molecules, these factors were further found to represent C3-like complement components [3,4]. Numerous attempts to identify the Ig-and TCR-like genes, using PCR or heterologous hybridization techniques, were also unsuccessful [7].…”
Section: Introductionmentioning
confidence: 98%
“…Only mediators of innate immunity, such as certain complement components, have so far been characterized in these species [3][4][5][6]. Both lamprey and hagfish are able to produce humoral factors in response to a number of antigens.…”
Section: Introductionmentioning
confidence: 99%